NON-TIMBER FOREST PRODUCT (NTFP) COMMODITIES HARVESTED AND MARKETED BY LOCAL PEOPLE AT THE LOCAL MARKETS IN MANOKWARI – WEST PAPUA - Wahyudi, Wahyudi (Association of Indonesian Forestry and Environment Researchers and Technicians, 2017)
The biodiversity richness of tropical forests in Papua provides substantial livelihood necessities for most forest people. This includes Non-Timber Forest Products (NTFPs), under-valued, neglected, or minor forest commodities that play a key role for the entire livelihood of the forest people. This paper highlights the diversity of NTFP marketed by the local people of Papua at traditional markets in Manokwari, West Papua. Data were collected from twenty respondents selected randomly from two local markets at Manokwari and field visits to surrounding (primary or secondary) forests, and analyzed using simple statistical analysis. The result indicates that 29 NTFPs commodities were on the market, and grouped into vegetables (9), food (4), fruit (7), medicinal herbs (4), tools (3) and addictive material (2). These commodities give alternative incomes, create unskilled jobs to the female-forest dwellers at Manokwari, and provide daily fresh vegetables and nutritious products for local customers. The marketed NTFPs are harvested from surrounding primary or secondary forest areas of Manokwari. Banana is the most favorable commodity in high demand either serving as food or fruit. Sago (Metroxylon spp.) is the only commodity supplied from other areas out of Manokwari, mainly from Wondama, Biak, Jayapura, and Serui. Annual events of Christmas and New Year create the highest demand for sago processed to papeda, that represent cultural or heritage food for most of the Papuanese family gatherings.